Analisis Yuridis Penyelesaian Wanprestasi dalam Perjanjian Jual Beli Rumah - Ikhlas Muhammad; Fadlan Fadlan; Christiani Prasetiasari; Siti Nurkhotijah (Penerbit Goodwood, 2023)
Purpose: The aim of this research is to determine the legal arrangements for resolving defaults in house sale and purchase agreements and to determine the implementation, obstacles, and solutions for resolving defaults in house sale and purchase agreements. Research methodology: The method used was empirical juridical research, namely research through a series of field interviews with respondents and informants. In addition, it uses normative research, namely research, through a literature study. Results: The results show that the legal regulation for settling defaults in house sale and purchase agreements, namely the Civil Code, regulates the obligations and rights of each party in the agreement. The settlement of defaults is regulated in Article 1239 of the Civil Code, which states that for each agreement to do something or not to do something, if the debtor does not fulfill his obligations, he will receive a solution in the form of an obligation to provide compensation for costs, losses, and interest. Limitation: Overall, this research provides valuable insights into legal arrangements for resolving defaults in house sale and purchase agreements, highlighting the importance of legal awareness and effective enforcement mechanisms in ensuring smooth and fair transactions between parties. Contribution: This research useful reference for policymakers and legal practitioners to improve the legal framework for house purchase and sale agreements.